Effect of water activity and pH on growth and toxin production by Clostridium botulinum type G - Briozzo, J. (1986)
The combined effect of water activity (a(w)) and pH on growth and toxin production by Clostridium botulinum type G strain 89 was investigated. The minimum a(w) at which growth and toxin formation occurred was 0.965, for media in which the pH was adjusted with either sodium chloride or sucrose. The minimum pH (at the optimum a(w)) for growth and toxin production of C. botulinum type G was found to be 5.6. Optimum conditions for toxin activation were a trypsin concentration of 0.1%, a pH of the medium of 6.5, and an incubation for 45 min at 37° C. These data did not show evidence of heat-labile spores, since a heat shock of 75°C for 10 min did not significantly decrease the spore count of strain 89G in media at pH 7.0 or 5.6. It was frequently observed that cells grown at reduced a(w) or pH experienced severe morphological changes.